Diseño y construcción de una bloquera para la fabricación de adoquines de concreto con materiales reciclados (2020)
The present research aims to cover the main aspects that acquire interference when designing and building tools necessary to increase productivity, efficiency, among other aspects, of the different productive sectors, one of them the construction sector, and in turn the materials used, the cobblestone represents an opportunity to build quality structures with a reduction in production costs, that is why policies must be increased, strategies, programmes focused on technological development and innovation, thus solving these questions of general interest. What are the technical and electromechanical criteria to be taken into account for the design and construction of a block machine for the manufacture of pavers with recycled materials? Having as answer the step by step of the construction of the blocking machine applying electromechanical criteria and making known different compositions for the test of the mixture rubber-platico, cement, gravel and sand with a very minimal amount of water. With this the design of the operating and maintenance manuals to have in good condition the functional part of the locking machine.